2018
DOI: 10.1002/app.46517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the filler size on the electrical percolation threshold of carbon black–carbon nanotube–polymer composites

Abstract: The Monte Carlo simulation of filled conductive polymer materials is a method of continuously generating a random conformation and averaging the interesting results to simulate the random dispersion of fillers in space. In our simulation, the irregular shapes of the filler were abstracted into regular ones. Carbon black (CB) aggregates were modeled as spheres, and carbon nanotubes (CNTs) were modeled as capped cylinders. The connection of the fillers was estimated via the calculation of the shortest distance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…While enhanced electrical conductivities are attained using secondary filler systems based on the excluded volume theory 11,12,15,16,18,19 , the decreased electrical conductivities are also observed because of the prevention of the interconnection between CNTs despite their similarity in structure and materials 2022 . Although there have been successful trials with theoretical models in second-filler composite systems 15,2329 , these two opposite tendencies ((1) increased conductivity due to the reduction in free volume of the polymer matrix and (2) decreased conductivity due to the disruption of CNT networks) are not well understood. In addition, it remains unanswered how the dimension of second fillers affect the electrical conductivity of the second-filler composite systems.…”
Section: Introductionmentioning
confidence: 99%
“…While enhanced electrical conductivities are attained using secondary filler systems based on the excluded volume theory 11,12,15,16,18,19 , the decreased electrical conductivities are also observed because of the prevention of the interconnection between CNTs despite their similarity in structure and materials 2022 . Although there have been successful trials with theoretical models in second-filler composite systems 15,2329 , these two opposite tendencies ((1) increased conductivity due to the reduction in free volume of the polymer matrix and (2) decreased conductivity due to the disruption of CNT networks) are not well understood. In addition, it remains unanswered how the dimension of second fillers affect the electrical conductivity of the second-filler composite systems.…”
Section: Introductionmentioning
confidence: 99%
“…Both experiments and simulations show different CB sizes leading to an important influence on percolation properties of composites, not only electrical percolation thresholds but also the rate of conductive curve . Thus, a suitable model size for simulation is researched by experiments first and CB (SPC Chemical Company, Stockholm, Sweden) is used in experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, large lateral size of GNP is favourable for electrical conductivity. Theoretical studies by Huang et al and Martin et al also found that in a polymer matrix containing carbon nanotubes (CNT), the electrical percolation threshold decreased with higher CNT aspect ratios [30,37].…”
Section: Electrical Conductivitymentioning
confidence: 99%